2012
DOI: 10.5713/ajas.2012.12076
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Gene Expression in the Uterine Endometrium during the Implantation Period in Pigs

Abstract: During embryo implantation in pigs, the uterine endometrium undergoes dramatic morphological and functional changes accompanied with dynamic gene expression. Since the greatest amount of embryonic losses occur during this period, it is essential to understand the expression and function of genes in the uterine endometrium. Although many reports have studied gene expression in the uterine endometrium during the estrous cycle and pregnancy, the pattern of global gene expression in the uterine endometrium in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…In restricted‐diet‐fed gilts, when compared to a normal‐diet‐fed gilts, out of 1690 genes, 976 genes were downregulated and 714 genes were upregulated. It is worth to note that in general, during the peri‐implantation period, endometrial genes were mostly downregulated when compared to the endometrium of non‐gravid pigs (Franczak et al., ; Kim et al., ; Østrup, Bauersachs, Blum, Wolf, & Hyttel, ). Observed in our study, decreased activity of a majority of genes in gravid endometrium harvested from a restricted‐diet‐fed gilts may contribute to deregulation of crucial processes occurred in the tissue that affects the proper intrauterine milieu.…”
Section: Discussionmentioning
confidence: 99%
“…In restricted‐diet‐fed gilts, when compared to a normal‐diet‐fed gilts, out of 1690 genes, 976 genes were downregulated and 714 genes were upregulated. It is worth to note that in general, during the peri‐implantation period, endometrial genes were mostly downregulated when compared to the endometrium of non‐gravid pigs (Franczak et al., ; Kim et al., ; Østrup, Bauersachs, Blum, Wolf, & Hyttel, ). Observed in our study, decreased activity of a majority of genes in gravid endometrium harvested from a restricted‐diet‐fed gilts may contribute to deregulation of crucial processes occurred in the tissue that affects the proper intrauterine milieu.…”
Section: Discussionmentioning
confidence: 99%
“…A stable adhesion between conceptus and endometrium requires reduction in mucin-1 on the apical surface of epithelium Furthermore, growth factors, cytokines and its receptors are all involved in embryo-maternal interactions 9 10 . In response to these factors, the uterine endometrial undergoes dramatic morphological and functional changes to be more easily receptive to the conceptus development 11 . Thus, to increase the rate of successful implantation, it is essential to understand the mechanism of the genetic regulation of endometrial changes.…”
mentioning
confidence: 99%
“…In addition, a recent study by Chen et al () revealed that the “immune response” is highly overrepresented for genes specifically upregulated in endometrial attachment sites. However, many previous studies have also demonstrated that the biological function of immune cells is decreased in the endometrium on Day 12 of pregnancy, and during the implantation period in pigs, maternal immune suppression contributes to the establishment of pregnancy (Bischof, Lee, Lee, & Meeusen, ; Kim et al, ). “ECM‐receptor interaction” was the common pathway among these three comparison groups.…”
Section: Discussionmentioning
confidence: 99%